MAKNA KIAS DAN IDIOM BERMETAFORA DALAM BUKU HIDUP ITU HARUS PINTAR NGEGAS DAN NGEREM KARYA EMHA AINUN NAJIB: KAJIAN SEMANTIK - Ahlan Romadhona; Rani Jayanti (CV. Denasya Smart Publisher, 2026)
The book Hidup Itu Harus Pintar Ngegas dan Ngerem by Emha Ainun Najib is a reflective work that employs symbolic language to convey ideas about life balance, spiritual awareness, and human values. This study aims to describe the types of semantic meanings and to reveal the moral and spiritual messages embedded in the reflective language of the book. This research adopts a qualitative approach with a descriptive-analytical method. The data consist of selected sentences and expressions containing figurative meaning, conceptual metaphors, conceptual–religious meaning, and metaphorical idioms. Data were collected through close reading and note-taking techniques, while data analysis was conducted contextually based on semantic theory. The findings indicate that the language used in the book is dominated by figurative meaning and conceptual metaphors that function to map abstract concepts of life and faith into concrete everyday experiences. In addition, conceptual–religious meanings and metaphorical idioms are used to convey ethical values, Sufi perspectives, and social criticism indirectly. These findings confirm that Emha Ainun Najib’s reflective language serves as a medium of contemplation and life learning that emphasizes the balance between courage and self-control.